Hypermethylation of CD19 promoter enables antigen-negative escape to CART-19 in vivo and in vitro - Ledererova, Aneta; Dostalova, Lenka; Kozlova, Veronika; Peschelova, Helena; Ladungova, Adriana; Culen, Martin; Loja, Tomas; Verner, Jan; Pospisilova, Sarka; Smida, Michal; Mancikova, Veronika (Journal for immunotherapy of cancer, 2021)
BACKGROUND: Anti-CD19 chimeric antigen receptor T cells (CART-19) frequently induce remissions in hemato-oncological patients with recurred and/or refractory B-cell tumors. However, malignant cells sometimes escape the immunotherapeutic targeting by CD19 gene mutations, alternative splicing or lineage switch, commonly causing lack of CD19 expression on the surface of neoplastic cells. We assumed that, in addition to the known mechanisms, other means could act on CD19 to drive antigen-negative relapse. METHODS: Herein, we studied the mechanism of antigen loss in an in vivo CD19-negative recurrence model of chronic lymphocytic leukemia (CLL) to CART-19, established using NOD-scid IL2Rgnull mice and HG3 cell line. We validated our findings in vitro in immortalized B-cell lines and primary CLL cells. RESULTS: In our in vivo CLL recurrence model, up to 70% of CART-19-treated mice eventually recurred with CD19-negative disease weeks after initial positive response. We found that the lack of CD19 expression was caused by promoter DNA hypermethylation. Importantly, the expression loss was partially reversible by treatment with a demethylating agent. Moreover, this escape mechanism was common for 3 B-cell immortalized lines as well as primary CLL cells, as assessed by in vitro coculture experiments. CONCLUSIONS: Epigenetically driven antigen escape could represent a novel, yet at least partially reversible, means of CD19 loss to CART-19 in B-cell tumors.
Keywords: translational medical research; Humans; receptory antigenů T-buněk; antigens; B-lymphocytes; receptors; Female; lidé; zvířata; Antigens, CD19; myši; hematologic neoplasms; Mice; Receptors, Antigen, T-Cell; DNA Methylation; metylace DNA; ženské pohlaví; Male; antigeny CD19; chimeric antigen; Animals; mužské pohlaví